THE FORMATION, CURRENT STATE AND PROSPECTS OF THE METHODS OF MATHEMATICAL DEVELOPMENT OF PRESCHOOL CHILDREN - Y.K Sadikova; Sh.Z Murtazayeva (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
Mathematical development of preschool children in the article about E.I.Tikheeva made a certain contribution to the development of methods for calculating children, determining the amount of knowledge available to” preschool children". He paid great attention to introducing children to the relationship between objects of different sizes: more — less, wider — narrower, shorter — longer, etc. An excellent master practitioner with a deep knowledge of the child, he felt the need for training, a consistent complication of educational material, although he mainly recognized only individual education